PUSAT REHABILITASI MENTAL DENGAN PENDEKATAN HEALING ENVIRONMENT - Annisa, Dwi Aprilia; Rahman, Akbar (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Mental health is no less important than physical health, but it is still not paid attention to by the people of Indonesia. The lack of mental health services and facilities is also a factor in the increase in cases of mental disorders, so it is deemed necessary to have mental health facilities with adequate facilities and infrastructure. To achieve this, The Healing Environment method can be applied to support the patient’s recovery rate. The healing environment method is related to stimulation of the human senses. The application of natural elements that can stimulate the senses of hearing, sight, touch and smell can increase the sharpness of the patient’s perception so that it can improve the patient’s recovery.